Ultrasonic tomography system: optimizing the frequency in a metal pipe conveyor - Abbaszadeh, J. (2013)
Ultrasonic Tomography has a dominant role in industry to generate cross sectional images of any object. In this paper, method of designing an Ultrasonic Tomography System due to the propagation manner of ultrasonic wave inside the various materials is investigated. The correct method of mounting of Ultrasonic sensors and behavior of the ultrasonic wave propagation in different layers has been simulated by the use of finite element software (COMSOL Multiphysics 3.5). To increase in practical nondestructive evaluation and inspection, we should increase our understanding of the basic physics and wave mechanics associated with guided wave inspection. A suitable ultrasonic sensor base on its efficiency and satisfying the simulation criteria is found and practically implemented on the surface of metal pipe. it is done by estimating the resonance frequency of sensor due to manner of ultrasonic wave propagation in different frequencies shown in simulation results. The proposed optimum frequency for the applied sensors is 40 kHz in which is tested practically and experimental results prove the high efficiency of this system.